Pemikiran Fikih Wanita Muhammad Shahrur - Nurlailatul Musyafa’ah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2010)
This article traces the thoughts of Muhammad Shahrur on the issue of women from the perspective of fiqh or Islamic jurisprudence. He stated that one aspect causing discrimantion toward Muslim women is the interpretation of medieval fuqaha (Muslim jurists) on certain Qur’anic verses which remain upheld by many Muslims up until today. This phenomenon, however, is contradictory to a widely held Islamic legal maxim stating that every social change necessitates the change in legal aspects. For the context of women issues, Islamic teachings should be reinterpreted for the purpose of relevance and modern demand. Using Western hermeneutic methodology, Muhammad Shahrur interprets Qur’anic verses, especially those related to women issues, such as the issue of inheritance, bequest, leadership, polygamy and dressing. In addition, he also proposes reform for laws affable to women. Although his thoughts are contradictory in many respects from the preposition of traditional Islamic jurisprudence, he has indeed opened a new perspective in the discourse of Islamic thoughts.